Caspase 3-specific cleavage of ubiquitin-specific peptidase 48 enhances drug-induced apoptosis in AML - Zhanglin Zhang; Xiang Lin; Yaling Yang; Xuemei Wang; Yi Wang; Xianbao Huang; Miao Hong; Wei Gao; Hua He; M. James You; Yi Yang; Guangyao Kong (Cancer Biology & Therapy)
Dysfunction or dysregulation of deubiquitination is closely related to the initiation and development of multiple cancers. Targeted regulation of deubiquitination has been recognized as an important strategy in tumor therapy. However, the mechanism by which drugs regulate deubiquitinase is not clear. Here, we identified ubiquitin-specific peptidase 48 (USP48), a member of the ubiquitin-specific protease family highly expressed in various tumors, as a specific substrate for the activated caspase-3. During drug induced apoptosis of AML cells, activated caspase-3 cleaves USP48 through recognizing the conservative motif DEQD located at 611–614 sites of human USP48. Subsequent analysis showed that the cleavage USP48 N-terminal fragment which contains catalytic active domain is easily degraded by ubiquitination. Meanwhile knockdown experiment showed that inhibiting the expression of USP48 could also promotes apoptosis and enhance the efficacy of chemotherapy drugs. Altogether, these results suggest that targeting USP48 may represent a novel therapeutic strategy in AML.